Innovative Knowledge Management in Minangkabau: A Comparative Study of Librarians and Teachers for Literacy Improvement - Resty Jayanti Fakhlina; Septevan Nanda Yudisman; Lailatur Rahmi; Ghazali Mohamed Fadzil; Fitri Ramadhani; Sabrina Latifa Zahra (Mimbar Agama dan Budaya, 2024)
This study aims to explore and compare knowledge management practices in Minangkabau, implemented by librarians and classroom teachers in the context of primary education, and their impact on improving students' literacy skills. Knowledge management has significant potential in optimizing learning outcomes through effective knowledge management. This research uses a qualitative method with a comparative approach to understand the best strategies for improving student literacy. Results suggest that librarians have a better literacy skill level than teachers. Through comparative analysis between librarians and classroom teachers, it is hoped that it can provide in-depth insights into effective collaboration and how to overcome challenges in improving the quality of literacy in primary schools.